THE ADVOCATES' IMMUNITY RIGHTS IN INDONESIA'S CRIMINAL JUSTICE SYSTEM - Mas Rara Tri Retno Herryani; Alwan Hadiyanto; Mas Subagyo Eko Prasetyo; Agus Saepul Alam (Jurnal Pembaharuan Hukum, 2023)
The purpose of this study is to determine the factors causing the lack of protection of advocates' immunity rights in the criminal justice process, and to analyze the future protection of advocates' immunity rights in the criminal justice system. The approach method used in this research is empirical juridical method. In the future advocate immunity rights can be used adversarial system. Where the in-adversarial system can be subject to immunity. That the judge here is only a jury between the advocate and the public prosecutor who is trying to prove the charges and charges filed at trial. if there is a violation of the code of ethics, for example an Advocate is attacked or criminalized by the opposing party, then with this advesari system the advocate can prove that what an Advocate does is in accordance with the procedures and rules of law that apply is a system that is a legal umbrella for an Advocate where the Advocate can prove what he does in carrying out his profession in accordance with the law.